The impact of Jinlida on blood glucose control and insulin resistance in patients with prediabetes and type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials - Li, Limeng; Tan, Qingyin; Zhang, Shidong; Huang, Yingxue; Xu, Chuhan; Fan, Shun; Li, Huanan; Tan, Tao (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the efficacy and safety of Jinlida (JLD) in improving glycemic control and insulin resistance in patients with prediabetes (PD) and type 2 diabetes mellitus (T2DM) through a meta-analysis of randomized controlled trials (RCTs).MethodsDatabases including PubMed, Web of Science, Cochrane Library, Embase, Scopus, CBM, CNKI, Wanfang, and VIP were searched up to July 2025. Randomized controlled trials comparing JLD with controls were included. Pooled analyses were conducted using a random-effects model. Pre-specified subgroup analyses included health status and treatment duration. Additional analyses by baseline FBG level and age were performed to explore residual heterogeneity. Multivariable meta-regression with Knapp-Hartung adjustment further examined potential moderators (e.g., background therapy, baseline FBG level). Publication bias was assessed by funnel plots, Egger’s test, and the trim-and-fill method. Risk of bias and evidence certainty were evaluated using RoB 2.0 and GRADE.ResultsA total of 20 RCTs involving 2,993 participants were included. Compared with controls, JLD significantly reduced: FBG (MD = -0.97, 95% CI: -1.40 to -0.53; p < 0.001), 2h-PG (MD = -1.52, 95% CI: -1.89 to -1.16; p < 0.001), HbA1c (MD = -0.76, 95% CI: -1.00 to -0.52; p < 0.001), HOMA-IR (MD = -0.78, 95% CI: -1.12 to -0.44, p < 0.001). In lipid outcomes, JLD improved: HDL-C (MD = 0.22, 95% CI: 0.12 to 0.32, p < 0.001), LDL-C (MD = -0.69, 95% CI: -1.05 to -0.33; p < 0.001), TC (MD = -0.57, 95% CI: -0.87 to -0.27; p < 0.001), TG (MD = -0.52, 95% CI: -0.72 to -0.31, p < 0.001). Subgroup analyses revealed that JLD produced greater glycemic improvements in shorter-duration trials and in patients with higher baseline fasting glucose (≥10 mmol/L). T2DM patients showed more pronounced reductions in HbA1c, HOMA-IR, and lipid parameters compared with PD. Additionally, JLD significantly improved HDL-C, LDL-C, TC, and TG, with lipid benefits being stronger in T2DM.ConclusionJLD may help improve glycemic control, insulin resistance, and lipid profiles in patients with T2DM and prediabetes. Given the varying levels of certainty in the evidence across outcomes, these findings should be interpreted cautiously. Further large-scale, high-quality RCTs are needed to confirm these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251124510.